ANALISA STATUS, KEDUDUKAN, DAN PEKERJAAN PEGAWAI TIDAK TETAP DALAM UU No. 5/2014 TENTANG APARATUR SIPIL NEGARA (ANALYSIS OF STATUS, POSITION, AND LEGAL STANDING OF TEMPORARY EMPLOYEE IN ACT OF 5/2014 ABOUT STATE CIVIL APPARATUS) - Wasisto Raharjo Jati (Pusjar SKPP Lembaga Administrasi Negara, 2015)
This article aims to analyze comparatively towards the status and position of temporary employees in Act of 43/1999 and government employees with contract agreements in Act of 5/2014. Analysis has focused on the main duties and functions of state / country and its standings in state employee management. The results of this study indicate that there is evolution in analyzing non-permanent employees form theLaw No. 43/1999 and the latest replacement rules which is Act of 5/2014. The lack of clarity regarding the status, position, and the fate of temporary employees,which has not previously accommodated in Employment Act, has been clarified in the Act of 5/2014.Keywords : Temporary Employee, Civil Services, Merit System, Bureaucracy SystemArtikel ini bertujuan untuk menganalisis tentang status dan kedudukan pegawai tidak tetap baik dalam Undang-Undang Nomor 43 Tahun 1999 dan Undang-Undang Nomor 5 Tahun 2014. Analisa yang ditampilkan berlokus kepada tugas pokok fungsi maupun status/kedudukannya dalam manajemen kepegawaian negara. Hasil penelitian ini menunjukkan bahwa terjadi evolusi dalam menganalisis pegawai tidak tetap dari Undang-Undang Nomor 43 Tahun 1999 hingga yang terbarukan dalam Undang-Undang Nomor 43 Tahun 1999. Ketidakjelasan mengenai status, kedudukan, nasib yang selama ini belum diakomodir dalam Undang-Undang Kepegawaian sebelumnya, kini sudah diperjelas semuanya dalam Undang-Undang ASN 2014 ini.Kata Kunci : Pegawai Tidak Tetap, Pegawai Negeri Sipil, Sistem Merit